Interface strength and mechanical properties of Inconel 718 processed sequentially by casting, milling, and direct metal deposition - Soffel, F.; Eisenbarth, D.; Hosseini, E.; Wegener, K. (Journal of materials processing technology, 2021)
Inconel 718 is the most commonly used nickel-based superalloy, mainly because it exhibits good weldability and can be processed by various types of manufacturing technologies. The combination of these processes with AM, typically referred to as hybrid manufacturing, can overcome limitations that exist in conventional process chains. However, different cooling rates of the material during hybrid manufacturing cause local variations in microstructure and mechanical properties within the components. Thus, quantification of the impact of individual process steps on the resulting properties could reveal most suitable process combinations. The present study focuses on the fabrication and repair of parts by casting, interface milling, and direct metal deposition (DMD). Four processing routes are investigated where heat treatment and interface conditions are varied before applying the DMD process. The cast components are either solution annealed or without heat treatment, and the interface to the DMD part remains either as-cast or it is milled. The results show that all conditions allow dense bonding between the cast section and the additively manufactured structure. The tensile properties of the test specimens exceed the level of conventionally cast parts and can be predicted by numerical simulation. The proposed combination of casting, milling, and DMD may therefore be applied to hybrid manufacturing process chains to increase the level of material efficiency and design flexibility.